Customer behavioral variables: a study in small and medium-sized commercial companies - Albano, Claudio Sonaglio; Ferreira, Evelise Pereira; Grabin, Fernanda Gobbi de Boer; da Silva, Yura José Caldeira (Revista Gestão da Produção Operações e Sistemas, 2023)
Purpose – The overall objective of this study was to identify the behavioral variables of customers of small and medium-sized commercial companies. Design/Methodology/Approach – To achieve the objective, qualitative research was carried out along with a bibliographic search and interviews were held with managers. The bibliographic research consisted of searching the historical records of all the National Meetings of Production Engineering and identifying work that addressed customer behavior. Regarding the interviews, the Delphi methodology was used to interview the managers of small and medium-sized commercial companies. Findings – After carrying out the bibliographic research, a total of fifty-eight behavioral variables were found that can influence the purchase decisions of customers. By applying a Delphi survey, it was possible to validate the behavioral variables found in the research of the literature and group them by consensus among managers. The research allowed the identification of which behavioral variables are most mentioned/valued by customers, and after that, managers were able to measure which are the most important variables in their segments and group them together. The results have the potential to support new strategies, aiming to support managers in their decision-making process. Originality/Value – This study has provided a broad knowledge about the different factors and variables that can influence the behavior of customers of small and medium-sized commercial companies. In addition, it validates the variables found in the literature. The Delphi methodology was applied through interviews with company managers, where it was possible to obtain a consensus between the behavioral variables, according to the opinion of the managers. Keywords – customer behavior, behavioral variables, bibliographic research, Delphi method, small and medium-sized companies.